A review of the use of ureolytic bacteria in the process of biocementation of soils - Кусбергенова, Жанар; Tulebekova, Асель; Zhumadilov, Ильяс (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
Today, various methods are used to improve the properties of soils, but scientists are constantly searching for an alternative technique that can improve the condition of the soil with minimal disturbance to the ecology, reducing the negative impact on the ecosystem and preserving it. Biocementation carried out by various microorganisms under given conditions fulfils all these requirements. This paper gives an overview of the proposed biocementation methods using bacteria capable of producing urease by microbially induced carbonate precipitation. Although numerous in vitro studies have demonstrated the success of the biocementation process as an environmentally friendly construction method, the application of this strategy in practice and in the field is still an unsolved problem. This is due to two main difficulties: firstly, biocementation is a complex phenomenon depending on many factors, and secondly, different types of microorganisms and different conditions have been considered in the scientific literature, resulting in a diversity of results. The presented work allows us to explore recent advances in the application of the widely used bacteria Sporosarcina pasteurii, Bacillus cereus and Bacillus paramycoides. The work also identifies directions for future research to expand the application of this method.